The interruption of the course of prescription of a criminal complaint in a canon criminal action - Borek, Dariusz (Prawo Kanoniczne, 2020)
The institution of prescription belongs to the field of issues rarely discussed by canon law. It is especially true about the interruption (suspension in particular) of the course of prescription. It should be noticed that the institution of interruption, and especially suspension, is weakly emphasised in both material and formal aspects of canon criminal law. In the context of relatively short terms projected currently for the prescription of actio criminalis, the issue of presumptive interruption (and/or suspension) of prescription becomes substantial. It should be stressed that the existing canon doctrine presents various opinions on when the proper interruption takes place. Such a lack of cohesion in the opinions forces the author of this article to answer the following questions: Is there any place in the canon law, both material and formal, for the institution of the interruption and/or suspension of prescription? If so, when exactly does it take place? And what effects does it have?